Hannah Arendt and the crisis of our time - Porcel, Beatriz (2013)
The notion of crisis is central to the work of Hannah Arendt, the word immediately refers to a sustained diagnosis of crises of modern times and the contemporary scene conjugated with the repeated analysis of the ‘crisis of judgment’ as relevant data of the totalitarian event. Moreover, the word crisis appears in the title of several articles and texts. The diversity of times and circumstances in which the qualification of crisis appears in Arendt’s work makes one wonder about the sense it takes, the various levels of analysis, the heuristic value it offers in order to assess its effects on modernity and on all aspects of human activity.